2017
DOI: 10.1121/1.4973624
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of pilot whale vocalization activity using hidden Markov models

Abstract: Vocalizations of cetaceans form a key component of their social interactions. Such vocalization activity is driven by the behavioral states of the whales, which are not directly observable, so that latent-state models are natural candidates for modeling empirical data on vocalizations. In this paper, we use hidden Markov models to analyze calling activity of long-finned pilot whales (Globicephala melas) recorded over three years in the Vestfjord basin off Lofoten, Norway. Baseline models are used to motivate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…We showed that this approach can be used to generate ethograms from animal-borne tag data, which is a key challenge to describe the behavior of free-ranging species (Sakamoto et al 2009). Such an approach could also be used to model, for example, the context specificity of vocalizations (Popov et al 2017), a subject of interest in social communication. Hidden Markov models account for the time series nature of the data explicitly, but a potential drawback is the simplistic first-order Markov aspect of the model that assumes that the underlying state probability is only dependent upon the previous state.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…We showed that this approach can be used to generate ethograms from animal-borne tag data, which is a key challenge to describe the behavior of free-ranging species (Sakamoto et al 2009). Such an approach could also be used to model, for example, the context specificity of vocalizations (Popov et al 2017), a subject of interest in social communication. Hidden Markov models account for the time series nature of the data explicitly, but a potential drawback is the simplistic first-order Markov aspect of the model that assumes that the underlying state probability is only dependent upon the previous state.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Le Strat & Carrat, 1999), ecology (pilot whale vocalization counts; Popov et al, 2017), and bioinformatics (T-lymphocyte counts; Marino et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1): clicks, whistles and pulsed calls 3,9,10 . Clicks are rapid and, usually, repetitive bursts of short, broadband sounds, primarily used for echolocation 1,11,12 ; whistles are continuous tonal sounds with few or no harmonics, possibly used for maintaining the cohesion of the group during foraging or travel 10,13,14 ; pulsed calls are rapidly broadband sound pulses, with distinct tonal properties caused by high pulse-repetition rates, possibly used for communication 3,10 . To obtain these conclusions, much significant work has been done: Kellogg et al 1 proved that clicks are used for echolocation by analysing the time-domain waveform of odontocetes' sound; Au et al 11 analysed the frequency spectra and source levels of clicks to prove that clicks can be used for echolocation; Fais et al 12 found that sperm whales use high-frequency, low amplitude clicks to provide high-resolution biosonar updates during the last stages of capture; Nemiroff 3 , Ford 10 , and Weilgart and Whitehead 13 obtained the conclusion that whistles and pulsed calls can be used for communication by analysing the time-frequency spectra of odontocetes sound; Popov et al 14 While the pilot whale sound was being recorded, the pilot whale kept swimming near the ship.…”
Section: Introductionmentioning
confidence: 99%
“…The pilot whale may use sound for a variety of purposes such as detecting partners or prey, communicating with each other etc.. However, it is very difficult to identify the specific purpose of a certain type of sound only by recording the sound and observing the swimming of the pilot whale 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation